2009
DOI: 10.1108/11766090910973920
|View full text |Cite
|
Sign up to set email alerts
|

Implementing IFRS in local government: value adding or additional pain?

Abstract: PurposeThe aim of this paper is determine the impact financial reporting obligations and, in particular, the International Financial Reporting Standards (IFRS) have on local government management decision making. In turn, this will lead to observations and conclusions regarding the research question: “Does reporting under the IFRS regime add value to the management of local government?”Design/methodology/approachFollowing analysis of a survey instrument distributed to all local governments in all states of Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…The underlying driver of incentives to smooth financial performance differs between the private and public sector. In a public sector environment the stewardship role is a greater function of management (Pilcher and Dean, 2009). Public sector management is perceived to have a greater responsibility to maintain assets under control, and use those assets effectively to deliver services in a balanced and value‐added manner (Lawton et al, 2000).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying driver of incentives to smooth financial performance differs between the private and public sector. In a public sector environment the stewardship role is a greater function of management (Pilcher and Dean, 2009). Public sector management is perceived to have a greater responsibility to maintain assets under control, and use those assets effectively to deliver services in a balanced and value‐added manner (Lawton et al, 2000).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…There are increasing pressures on public sector management to provide financial accounting information detailing a steady and predictable level of financial performance so as to demonstrate sound future fiscal sustainability (Pilcher and Dean, 2009). As noted above, external financial reporting (based on accrual‐based accounting principles) is becoming an essential element of the operational process of the public sector in nations such as Australia, plus of importance to decision‐making of external stakeholders.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of IFRS in the public (governmental) sector has not been widely researched except by Rixon and Faseruk (2009) in Canada, Pilcher and Dean (2009a, b) in Australia, and Heald and Georgiou (2009) in the UK. Rixon and Faseruk examined the impact of adoption of IFRS by Canadian public sector entities.…”
mentioning
confidence: 99%
“…Due to a lack of detailed guidance for public sector entities, the Canadian entities used diverse interpretations of IFRS that led to non‐comparable financial statements. Pilcher and Dean (2009b) investigated the implementation of IFRS in local government reporting in Australia and found that IFRS requirements for local government are time consuming and costly, adding little value to the management of local government and often causing decoupling of internal and external financial reports. Heald and Georgiou (2009) discussed conceptual, technical and timetable issues in relation to UK government accounts.…”
mentioning
confidence: 99%